Antimony speciation in soils, sediments and volcanic ashes by microwave extraction and HPLC-HG-AFS detection - Quiroz, Waldo; Astudillo, Francisco; Bravo, Manuel; Cereceda-Balic, Francisco; Vidal, Víctor; Palomo-Marín, María Rosario; Rueda-Holgado, Fernando; Pinilla-Gil, Eduardo (Microchemical journal, 2016)
On the 5th of May 2008, the first recorded eruption of the Chaitén Volcano in southern Chile occurred. Because one of the main natural sources of Sb is volcanic activity, it was necessary to study the distribution of Sb and its species in the nearby ecosystem. The present study aims to develop a methodology for total Sb determination by ICP-MS and a method for Sb(V) and Sb(III) determination by HPLC-HG-AFS in soils, sediments and volcanic ash. Microwave digestion in a 6mL HNO3 and 0.5mL HBF4 acid digestion mixture can achieve total solubilization of Sb in solid samples. Thirty minutes at 200°C with 100mmolL−1 of oxalic acid were suitable conditions for fast and efficient microwave extraction to obtain a good extraction yield. However, Sb(III) stabilization was strongly inhibited; thus, the mixture of 100mmolL−1+20mmolL−1 of ascorbic acid was the best for Sb solubilization and Sb(III) stabilization. A total of 1.8±0.1μgg−1 of Sb was quantified in the volcanic ash from the first eruption. The Sb concentrations in the sediments were 3 times higher than the Sb concentrations in the sediments from the reference zone. In the extracts of the volcanic ash and sediment, Sb(III) was the most abundant species, accounting for 70 to 97% of the total Sb found in the extracts. The results suggest that most of the Sb thrown from the Chaitén Volcano accumulated in the sediments at the mouths of the Yelcho and Chaitén Rivers, mainly in the form of Sb(III). •A methodology for Sb speciation in soils, sediments and volcanic ash was developed.•The effect of extracting agents over % extraction and stability of Sb species was studied.•100mmolL−1 of oxalic acid in 20mmolL−1 of ascorbic acid was the best condition.•Methodology was applied to samples impacted by Chaiten's volcano eruption.•We detect an enrichment of Sb(III) in sediments and volcanic ashes.